Peran Mahasiswa Magang Bagi UMKM Penyedia Jasa Digital Marketing “Diva Digital” Di Kecamatan Buduran, Kabupaten Sidoarjo - Ni Made Ida Pratiwi; Sarah Nabilla Khoirunisa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Digital marketing is a service practice used to market products or services using digital media. Analysis of product or service marketing services before digital marketing developed was to use traditional methods such as print media, radio and television. Marketing using this old method involves promotions carried out without using the internet. As technology develops, now marketing products or services so that they are quickly recognized by the wider community does not require high costs for printing or paying for advertisements on TV. Marketing products or services can be done using digital media or what is usually called digital marketing. One of the popular digital platforms that quickly makes something or a product viral is the TikTok application. Tiktok is a social media that also has a tiktokshop feature to facilitate e-commerce. Tiktokshop offers advantages in terms of wide audience reach, high engagement, and innovative advertising features. However, a month ago, on October 4, 2023, Tiktokshop officially closed its services. This closure has an impact on business actors who have relied on this platform to market their products. However, there are still many other digital platforms that can be used for marketing activities. Therefore, business actors must continue to follow developments in digital marketing trends and utilize platforms and e-commerce that suit their target audience.